Strategic Resource Extraction and Recycling from Waste: A Pathway to Sustainable Resource Conservation - Inna Pitak; Anastasiia Sholokhova; Arūnas Baltušnikas; Rita Kriūkienė (Resources)
This study examines calcium extraction from Bottom Ash (BA) and the use of Solid Residue (SR) as a substitute for White Lump Clay (WLC) in brick production. Experimental analyses identified calcium and silicon as the main elements in BA, with 50% of calcium carbonate recovered through leaching. SR was a viable alternative to WLC in ceramic bricks, as SEM-EDS and FTIR analyses revealed changes in composition and microstructure. This approach promotes circular economy principles by recovering resources and reducing waste. Calcium extraction from BA can produce 29,000 tons of CaCO3 annually for industrial use, while substituting SR for WLC in brick production could replace 30% of clay, saving 1500 tons of clay and producing millions of bricks annually. Less than 50% of incinerated Municipal Solid Waste (MSW) would require landfilling. The process supports sustainable construction by conserving natural resources, reducing landfill waste, and lowering CO2 emissions. It offers annual cost savings of 2,639,250 USD and preserves 74,812.5 tons of resources through waste and clay reduction. By demonstrating a scalable model for waste valorization, this research aligns with global goals for sustainable development, resource efficiency, and ecological balance.